2020
DOI: 10.23937/2469-567x/1510071
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Glucose Intolerance in HIV Infected Children on Antiretroviral Therapy at Lubango Pediatric Hospital - Angola

Abstract: Introduction: Antiretroviral therapy (ART) has proved to be an important intervention in the reduction of both morbidity and mortality of HIV infected patients. As the use of ART increases, a number of studies have associate it to some metabolic complications including glucose intolerance, dyslipidaemia, and diabetes mellitus. Despite the high prevalence of HIV/AIDS in Africa and the recent increased access to Antiretroviral drugs, information on ART related insulin resistance and glucose metabolism in the Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Our study has demonstrated that CALWH in Ghana exhibit elevated HbA1c levels. We observed a prevalence of insulin resistance of 22% based on the HOMA index, which is slightly higher than in previous studies conducted among children in sub-Saharan Africa (20%) [35]. However, a much higher prevalence has been reported in European children (52%) and adults in sub-Saharan Africa (47%) [21,36].…”
Section: Discussioncontrasting
confidence: 74%
“…Our study has demonstrated that CALWH in Ghana exhibit elevated HbA1c levels. We observed a prevalence of insulin resistance of 22% based on the HOMA index, which is slightly higher than in previous studies conducted among children in sub-Saharan Africa (20%) [35]. However, a much higher prevalence has been reported in European children (52%) and adults in sub-Saharan Africa (47%) [21,36].…”
Section: Discussioncontrasting
confidence: 74%
“…The results of both analyses correlate with each other, showing no significant changes. In a cross-sectional study in Angola ( Francisco et al, 2020 ), insulin resistance based on the homeostatic model (HOMA-R) was 20% and glucose intolerance was 40%. Two other cross-sectional analyses of longitudinal cohort and cohort studies conducted in Italy ( Rosso et al, 2007 ) and Rwanda ( Dusingize et al, 2013 ) compared median HOMA IR and fasting glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance, measured using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), is also common among HIV-infected children on ART. A recent study observed insulin resistance in 20% of the HEI children with clinical end stage of the disease and long-time on ART ( 38 , 77 ) ( Table 1 ). Changes in glucose transport and metabolism contribute to impaired insulin secretion by beta cells and altered glycogen synthesis in hepatocytes which significantly increase the risk of developing type 2 diabetes among PLWHA on ART ( 78 ).…”
Section: Mitochondria Are Regulatory Hubs For Cell Metabolism and Fun...mentioning
confidence: 97%